The Relative Impact of Bank Credit on Manufacturing Sector in Nigeria - Ume, Kalu Ebere; Obasikene, Alice Chinwe; Oleka, Chioma Dorothy; Nwadike, Augustina Ogoma; Okoyeuzu, Chinwe (International Journal of Economics and Financial Issues, 2017)
This study examined the relative impact of Bank credit on the manufacturing sector in Nigeria’ 1986-2013. The major objective was to investigate the extent of impact of bank credit on the output of the manufacturing sector in Nigeria. The Study adopted the ARDL bound cointegration test approach and error correction representations. Focusing on the short run relationship, we found every explanatory variable and their following lags as significant functions of Volume of Bank Credits (VBC) at 5% except Exchange rate and its lags. In the Bound Test following the ARDL, we found evidence in favor of cointegration among the variables regardless of whether they are stationary or not given that the observed test statistic exceeds the upper critical band. Our results imply the presence of co integrating vectors of long run equilibrium relationships among the variables of interest. This result is corroborated by the Dynamic OLS results as well as the long run estimates of the ARDL. Overwhelmingly, we found evidence of a certain return to the long-run equilibrium in the model. The error correction term is negative and statistically significant. The negative value shows that there exists an adjustment speed from short-run disequilibrium towards the long-run equilibrium. By this, there is an indication that it takes about three years to restore the long-run equilibrium state on the Output of the manufacturing should there be any shock from the explanatory variables. By way of policy recommendation or positioning, the Central Bank and other monetary authorities alike should make policy that will lead to increase in volume of bank credits to the manufacturing sector. As this will play a catalytic role for growth in the sector in particular and the economy in general. Keywords: Manufacturing sector, Volume of Bank credit, Nigeria, Autoregressive Distributed Lag Model JEL Classifications: E51, L6